1998
DOI: 10.1038/27655
|View full text |Cite
|
Sign up to set email alerts
|

Electric fish measure distance in the dark

Abstract: Distance determination in animals can be achieved by visual or non-visual cues. Weakly electric fish use active electrolocation for orientation in the dark. By perceiving self-produced electric signals with epidermal electroreceptors, fish can detect, locate and analyse nearby objects. Distance discrimination, however, was thought to be hardly possible because it was assumed that confusing ambiguity could arise with objects of unknown sizes and materials. Here we show that during electrolocation electric fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(145 citation statements)
references
References 20 publications
5
138
0
Order By: Relevance
“…Theoretical constructs indicate that beyond some critical distance, object images are similar to the image of a sphere (Sicardi et al, 2000). These predictions agree with the experimental data (Rasnow, 1996;Stoddard et al, 1999;Assad et al, 1999;Caputi et al, 2011) and led to an interesting series of behavioral experiments showing that a cube might be confused with a more closely placed sphere (von der Emde et al, 1998). The same reasoning allows one to predict that beyond some distance two objects should not be distinguished from a larger one and that location precision should decay with distance (Pereira and Caputi, 2010).…”
Section: Introductionsupporting
confidence: 78%
“…Theoretical constructs indicate that beyond some critical distance, object images are similar to the image of a sphere (Sicardi et al, 2000). These predictions agree with the experimental data (Rasnow, 1996;Stoddard et al, 1999;Assad et al, 1999;Caputi et al, 2011) and led to an interesting series of behavioral experiments showing that a cube might be confused with a more closely placed sphere (von der Emde et al, 1998). The same reasoning allows one to predict that beyond some distance two objects should not be distinguished from a larger one and that location precision should decay with distance (Pereira and Caputi, 2010).…”
Section: Introductionsupporting
confidence: 78%
“…This measure was shown to be size invariant and independent from movement direction (Hofmann et al, 2013). Thereby, the tSAR potentially is equally powerful for distance estimation as the pure spatial SAR measure (von der Emde et al, 1998). How well such measures can be used in the analysis of complex electric flow remains to be tested.…”
Section: Naturalistic Electric Flow Reconstruction and Analysismentioning
confidence: 99%
“…Electric image (EI) is a term used to describe the change of the voltage distribution across the animal's skin due to object-induced modulation in the self-generated electric field. At present we have only a basal understanding of which parameters of these, in many situations ambiguous, sensory images are relevant for behavior (Lewis and Maler, 2002;von der Emde et al, 1998). Most evidently, the location of a simple object can be detected by locating the peak modulation in the EI, while object distance can be estimated from the relative width of the EI.…”
Section: Sensory Flow In Weakly Electric Fishmentioning
confidence: 99%
“…Behavioral experiments have shown that these fish can discriminate the size and the shape of objects in the dark. In particular, in [von der Emde et al, 1998], biologists demonstrated that when perceiving an object a fish first identifies its electric nature, then localizes the object and finally recognizes the shape. This behavior is astonishing as it has been shown that using electric sense the separation between localization and object geometric properties is not obvious at all.…”
Section: Weakly Electric Fishmentioning
confidence: 99%